KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SMA DALAM MENYELESAIKAN MASALAH STATISTIKA DENGAN MEMANFAATKAN KECERDASAN BUATAN - Rodiyah Putri Aryffiani, Lisa`yiha; Yuli Eko Siswono, Tatag (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence provides opportunities for students to obtain assistance in solving various learning problems, including statistical problems. However, the use of AI also raises questions about how students’ critical thinking skills are demonstrated when interacting with such technology. Therefore, this study aimed to describe the critical thinking skills of high-, moderate-, and low-mathematical-ability senior high school students in solving statistical problems using Artificial Intelligence. This study employed a qualitative descriptive approach with a case study design. The research subjects consisted of three senior high school students representing high, moderate, and low mathematical abilities. Data were collected through a Mathematical Ability Test, a Critical Thinking Skills Test, an Artificial Intelligence usage questionnaire, and interviews. The data were analyzed through data reduction, data display, and conclusion drawing. The results showed that students with high mathematical ability used ChatGPT to obtain information that helped them understand the concepts required to solve statistical problems. Students with moderate mathematical ability used ChatGPT to support problem-solving and concepts understanding, although some concepts were not fully understood. Meanwhile, students with low mathematical ability used ChatGPT primarily to obtain formulas and information needed to solve the problems. Without using ChatGPT, students with high mathematical ability were still able to provide reasoning consistent with their analysis, whereas students with moderate and low mathematical ability showed limitations in providing justification and interpreting the results obtained. Thus, the use of ChatGPT provided different forms of support according to students’ mathematical abilities in solving statistical problems.